Influenza A Virus Infection in Domestic Ferrets - Kuroda, Yudai; Okada, Ai; Shimoda, Hiroshi; Miwa, Yasutsugu; Watamori, Akiko; Ishida, Hiroho; Murakami, Shin; Takada, Ayato; Horimoto, Taisuke; Maeda, Ken (Japanese Journal of Infectious Diseases, 2022)
Ferrets are animals that are known to be susceptible to influenza A virus (IAV) infection. To evaluate the risk of IAV transmission from diseased ferrets to humans, a survey was performed to detect specific antibodies against the H1, H3, H5, and H7 subtypes of IAV. Using enzyme-linked immunosorbent assay for hemagglutinin proteins, we found a high positive rate for the H1 (24.1%) and H3 (5.2%) subtypes. The results were confirmed by a virus neutralization test for representative antibody-positive serum samples. We also detected hemagglutinin and neuraminidase genes in two ferrets showing acute respiratory disease and whose owner was diagnosed with IAV infection; a human H1N1pdm virus was isolated from one of these ferrets. Our findings suggest that attention should be paid to IAV infection from humans to ferrets and vice versa.